2014
DOI: 10.1021/la502514e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis at the Air–Water Interface of a Two-Dimensional Semi-Interpenetrating Network Based on Poly(dimethylsiloxane) and Cellulose Acetate Butyrate

Abstract: The UV-induced cross-linking of methacryloxypropyl-terminated poly(dimethylsiloxane) oligomers was studied at the air-water interface either in pure PDMS Langmuir monolayers or in mixed films containing cellulose acetate butyrate. Surface pressure-area isotherms, area measurement at constant surface pressure, Brewster angle microscopy observations, and infrared-visible sum frequency generation (SFG) spectroscopy were combined to follow the evolution of the monolayers upon in situ UV photoirradiation. For both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…PDMS membranes with various thicknesses, widths, and porosities have been used for various applications, such as microvalves [3,4,5], micropumps [6,7], microlenses [8,9,10,11], and cell culture substrates [12,13]. The spin-coating [14,15], casting [16], and Langmuir–Blodgett methods [17,18] are mainly used for the fabrication of PDMS membranes. Among these, the spin-coating method is the most popular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDMS membranes with various thicknesses, widths, and porosities have been used for various applications, such as microvalves [3,4,5], micropumps [6,7], microlenses [8,9,10,11], and cell culture substrates [12,13]. The spin-coating [14,15], casting [16], and Langmuir–Blodgett methods [17,18] are mainly used for the fabrication of PDMS membranes. Among these, the spin-coating method is the most popular.…”
Section: Introductionmentioning
confidence: 99%
“…If a membrane casting machine is used, the membrane quality is uniform, but additional equipment is required. Furthermore, the Langmuir–Blodgett method can be used to fabricate a membrane by collecting the separated molecules of materials on water using a moving barrier [17,18]. Owing to the self-assembly effect, a well-aligned membrane can be fabricated on a molecular basis.…”
Section: Introductionmentioning
confidence: 99%
“…It is a powerful tool to transfer molecular monolayers from an air-water interface to a solid substrate. By first spreading and then compressing amphiphilic molecules at the airwater interface, one can fabricate monomolecular films, called Langmuir monolayers, that are highly ordered over areas of several hundreds of cm 2 [24]. In addition to producing films one single molecule thick, this technique has the advantage of controlling the density of molecules in the monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the SFG signal change from methacrylate contribution to PMMA contribution was used to monitor the cross-linking of methacryloxypropyl-terminated polydimethylsiloxane (PDMS) at the water–air surface using UV irradiation. It was found that such cross-linking occurred for PDMS monolayers as well as mixed monolayers of PDMS and cellulose acetate butyrate . These studies clearly demonstrated that polymethacryate surface structures can be perturbed by the side chain composition, and SFG can be used to monitor interfacial reactions involving methacrylate groups.…”
Section: Applications Of Sfg To Study Polymer Surfaces and Interfacesmentioning
confidence: 80%
“…It was found that such cross-linking occurred for PDMS monolayers as well as mixed monolayers of PDMS and cellulose acetate butyrate. 75 These studies clearly demonstrated that polymethacryate surface structures can be perturbed by the side chain composition, and SFG can be used to monitor interfacial reactions involving methacrylate groups.…”
Section: (11f)mentioning
confidence: 88%